2007
DOI: 10.1038/sj.ejcn.1602616
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diet and insulin-like growth factors in adulthood: 65-year follow-up of the Boyd Orr Cohort

Abstract: Objective: High levels of insulin-like growth factor-I (IGF-I) are associated with an increased cancer risk and reduce risk of diabetes and coronary heart disease. We investigated associations of diet in childhood, in particular energy intake, with the IGF system in adulthood to determine if IGF-I -disease associations could be linked to early nutrition. Design: Retrospective cohort study. Setting: Sixteen survey centres in England and Scotland that originally participated in the Carnegie (Boyd Orr) Survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
2
23
1
Order By: Relevance
“…Our finding of no association between BF and obesity in adulthood is in line with other studies of varying size, design, and confounder control (7,(29)(30)(31)(32)(33)(34), although one study suggested that BF was associated with an increased risk of obesity (35). Compared with many of these studies, an advantage of our study was the use of information on BF collected at the end of infancy compared with maternal recall later in childhood (31,33,34) or in adulthood (7,35).…”
Section: Breastfeeding and Obesitysupporting
confidence: 76%
“…Our finding of no association between BF and obesity in adulthood is in line with other studies of varying size, design, and confounder control (7,(29)(30)(31)(32)(33)(34), although one study suggested that BF was associated with an increased risk of obesity (35). Compared with many of these studies, an advantage of our study was the use of information on BF collected at the end of infancy compared with maternal recall later in childhood (31,33,34) or in adulthood (7,35).…”
Section: Breastfeeding and Obesitysupporting
confidence: 76%
“…Similar inverse findings are reported with respect to childhood diet and later IGF-I concentrations. Martin et al found that milk intake in childhood was inversely correlated with IGF-I concentrations 65 years later [13], and in childhood a high milk intake is associated with higher IGF-I levels [15]. Subjects randomized to receive milk supplementation of their diet during the first 5 years had significantly lower IGF-I levels at 25 years compared to controls indicating a down regulation of the IGF-I axis [16].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, early programming of the IGF-I axis may theoretically serve as a link between early life events and risk of adult life style diseases [7]. Furthermore, the IGF-I levels are strongly associated with height in childhood but not in adults [13].…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 prospective studies have addressed the long-term relevance of (animal) protein intake during growth and/or its sources in relation to the GH-IGF-I axis. Ben-Shlomo et al (16) and Martin et al (17) found an inverse association between milk intakes in early childhood and IGF-I concentrations in young adulthood (16) and older age (17). The authors proposed that this inverse relation reflects an early programming of the GH-IGF-I axis in response to higher (animal) protein intakes in early life.…”
Section: Introductionmentioning
confidence: 89%